Creative resources for elementary classrooms and school-age programs - Wheeler, Ron (Delmar Publishers, 1997)
Creative Resources for Elementary Classrooms & School Age Programs is the most comprehensive hands-on teaching resource available today for those working with elementary age students. This innovative textbook contains over 50 inventive themes with goals, activities, resources, bulletin board ideas, and a section on computers software. Students will learn all about the history of inventors and their inventions and how each relates across curriculum strategies such as writing, science, math, social studies, and music